2018
DOI: 10.18203/2394-6040.ijcmph20180781
|View full text |Cite
|
Sign up to set email alerts
|

ROME: a tool to train under graduate medical students as community health care providers

Abstract: Background: Re-Orientation of Medical Education (ROME) program is relatively a new teaching and learning method for undergraduate medical students which enables them to achieve the knowledge and skills to provide effective community health care. Objective of this study was to find out which of the various activities that were carried out during the ROME posting helped them to achieve the required knowledge and skills to provide effective Community Health Care.Methods: A descriptive study was conducted among 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
1
1
0
Order By: Relevance
“… 10 , 11 In Pondicherry and other states of India, other important mobile apps were used namely Epicollect5 and ROME as SDL tools for UG medical graduates. 4 , 17 – 20 In our study, 46% of students use smartphone apps at least once a day which is similar to other studies. 1 , 2 , 6 , 7 , 11 The students who have submitted their responses said that they found it to be very easy to install and user-friendly, during the research.…”
Section: Discussionsupporting
confidence: 89%
“… 10 , 11 In Pondicherry and other states of India, other important mobile apps were used namely Epicollect5 and ROME as SDL tools for UG medical graduates. 4 , 17 – 20 In our study, 46% of students use smartphone apps at least once a day which is similar to other studies. 1 , 2 , 6 , 7 , 11 The students who have submitted their responses said that they found it to be very easy to install and user-friendly, during the research.…”
Section: Discussionsupporting
confidence: 89%
“…[ 9 ] Many studies have shown that if education is research oriented and field based, students will not only gain knowledge but also learn the clinical skills and research methodology. [ 10 11 ] During the re-orientation of medical education (ROME)[ 12 13 14 15 ] posting of undergraduate medical students in the Department of Community Medicine, a field-based activity was planned and data were collected by the students using a smartphone app under the guidance of faculty and postgraduate students. Keeping the importance of students’ feedback in mind, the current study was planned with an objective to understand the students’ perception on using smartphone app as a tool for data collection in the field of community research.…”
Section: Introductionmentioning
confidence: 99%